2018
DOI: 10.1111/1556-4029.13737
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Chronological Age from Postmortem Tissues Based on Amino Acid Racemization

Abstract: Skin and cartilage tissue specimens from 32 male and 13 female corpses aged between 17 and 50 years were collected within 24 h after the death. Each specimen was analyzed for the composition of dextro (D) and levo (L) forms of aspartate, glutamate, and alanine. Linear regression models were constructed using ln [(1 + D/L)/(1 - D/L] equation to define the relationship between the extent of racemization and the chronological age. Aspartate D/L rates from cartilage showed high correlation (r = 0.779, p < 0.001, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
5
0
3
Order By: Relevance
“…Morfološke metode korištene u procjeni dentalne dobi često su neprecizne jer su subjektivne, odnosno ovise o iskustvu forenzičnog stomatologa. Biokemijske su metode, s druge strane, objektivne jer se rezultati dobivaju na osnovi specifičnih kemijskih postupaka s kvantificiranim rezultatom 34,35 . Starenjem tkivni proteini prolaze kroz niz neenzimatskih, spontanih reakcija.…”
Section: Racemizacija Asparaginske Kiselineunclassified
See 2 more Smart Citations
“…Morfološke metode korištene u procjeni dentalne dobi često su neprecizne jer su subjektivne, odnosno ovise o iskustvu forenzičnog stomatologa. Biokemijske su metode, s druge strane, objektivne jer se rezultati dobivaju na osnovi specifičnih kemijskih postupaka s kvantificiranim rezultatom 34,35 . Starenjem tkivni proteini prolaze kroz niz neenzimatskih, spontanih reakcija.…”
Section: Racemizacija Asparaginske Kiselineunclassified
“…Dakle, što je osoba starija, u tkivima će imati veći udio D-forme aminokiselina. Smrću se ovaj proces zaustavlja 35,36 . Asparaginska kiselina je aminokiselina koja ima najveći stupanj racemizacije i zbog toga se koristi u ovim mjerenjima 37 .…”
Section: Racemizacija Asparaginske Kiselineunclassified
See 1 more Smart Citation
“…A current summary of the correlation coefficients between AAR rate and actual age in various studies found in the literature has been provided by Tiplamaz et al. .…”
Section: Relation To Other Dating Techniquesmentioning
confidence: 99%
“…A number of previous studies on cartilage tissues with forensic applications have reported a high or moderate correlation between the Asp racemization rate and age . A recent study was conducted to compare the correlation of the racemization rates of Asp, Glu, and Ala amino acids from postmortem tissues (specifically ear cartilage and gluteal skin tissues) to a human's chronological age . A current summary of the correlation coefficients between AAR rate and actual age in various studies found in the literature has been provided by Tiplamaz et al.…”
Section: Relation To Other Dating Techniquesmentioning
confidence: 99%